Magnetic degradable starch microsphere with core-shell structure as well as preparation method and application of magnetic degradable starch microsphere
By using core-shell structure and specific crosslinking agents in magnetic degradable starch microspheres, the microsphere stability and toughness problems caused by magnetic nanoparticle embedding in the prior art are solved, and efficient embolization, chemotherapy and heat are achieved The therapeutic effect and ensures the biocompatibility of the microspheres and catheter passivity.
Patent Information
- Application Number
- CN202411319681.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-27
AI Technical Summary
The existing design of magnetic nanoparticles embedded in embolized microspheres, which makes it difficult to degrade materials and lead to residual in the body, which may cause foreign body inflammation. Embedding magnetic nanoparticles will increase the strength of the microspheres but reduce toughness, resulting in the delivery of microspheres. It is prone to agglomeration or blockage of the catheter during the process.
Magnetic degradable starch microspheres with core-shell structure are adopted to control the amount of crosslinking agent in the inner and outer layer, and the magnetic nanoparticles are embedded in the core with low crosslinking degree to form a shell with high crosslinking degree to ensure that the microspheres have both Strength and toughness, and the introduction of phosphate drug-loaded groups through specific crosslinking agents to achieve synergistic treatment of thermotherapy, chemotherapy, and embolism.
The stability of microspheres and catheter passability are achieved, ectopic diffusion and foreign body inflammation are avoided, and the excellent biocompatibility and functional effect can be used to rapidly degrade the core after the shell is completely degraded, ensuring embolization effect and drug loading. Medication ability.
Smart Images

Figure CN119185240A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of embolic microspheres, and in particular to a magnetic degradable starch microsphere with a core-shell structure, and a preparation method and application thereof. Background Art
[0002] Transcatheter arterial chemoembolization (TACE) is a treatment method for cancer tumors. It is achieved by placing a catheter in the target artery and introducing embolic materials through the catheter to block the blood circulation and nutrient supply of the cancer tumor to inhibit tumor growth. Embolic materials can be loaded with chemotherapy drugs. Ideal embolic materials need to have the following properties: a) they can pass through the catheter smoothly without sticking or clogging; b) they are non-immunogenic and have good biocompatibility; c) their size can adapt to the target blood vessels and block the blood oxygen supply. Magnetic induction hyperthermia is a new tumor treatment strategy that can use magnetic nanoparticles to convert electromagnetic energy into heat under the action of an alternating magnetic field to induce tumor cell apoptosis or necrosis, significantly improving the tumor treatment effect. Combining materials that can respond to hyperthermia with TACE's embolic microspheres can achieve the purpose of synergistic treatment of embolism, chemotherapy, and hyperthermia.
[0003] In the prior art, it has been reported that magnetic nanoparticles are embedded in drug-loaded embolic microspheres, so that the microspheres themselves have nuclear magnetic imaging capabilities, thereby realizing the "three-in-one" synergistic diagnosis and treatment integration of magnetic induction hyperthermia, chemotherapy and embolization. However, in the currently published literature or patents, most of the designed microsphere skeletons are difficult to degrade polylactic acid-glycolic acid copolymer (PLGA) or silica materials, which remain in the body for a long time and pose a hidden danger of foreign body inflammation. Although a small number of studies have used degradable materials to embed magnetic nanoparticles to prepare magnetic degradable microspheres, since embedding magnetic nanoparticles will increase the strength of the microspheres while reducing the toughness of the microspheres, it is difficult to control them synergistically, resulting in the risk of magnetic particle leakage in the microspheres, and they cannot be stored for a long time, and they are prone to agglomeration or clogging the catheter during delivery. Summary of the invention
[0004] In order to solve the above technical problems, the purpose of the embodiments of the present application includes providing a magnetic degradable starch microsphere with a core-shell structure and a preparation method and application thereof.
[0005] In a first aspect, the present application provides a method for preparing magnetic degradable starch microspheres with a core-shell structure, comprising the following steps: aqueous phase configuration: mixing a first starch, magnetic nanoparticles and a first cross-linking agent in a certain proportion to obtain an aqueous phase;
[0006] Oil phase preparation: mixing an oil-soluble solvent and an oil-soluble dispersant to obtain an oil phase;
[0007] Reverse suspension polymerization: adding the water phase to the oil phase, reacting for a period of time, adding a second cross-linking agent and a second starch, heating to a predetermined temperature, and obtaining magnetic degradable starch microspheres with a core-shell structure after the reaction is completed;
[0008] Among them, the mass ratio of sodium trimetaphosphate to sodium tripolyphosphate in the first cross-linking agent is (5-15):(85-95), and the mass ratio of sodium trimetaphosphate to sodium tripolyphosphate in the second cross-linking agent is (85-95):(5-15).
[0009] In the above technical solution, by controlling the amount of crosslinking agent in the inner and outer layers, a microsphere structure with a high crosslinking outer shell and a low crosslinking inner core is obtained. The magnetic nanoparticles are embedded in the inner core with a low crosslinking degree, so that the microspheres have both magnetic imaging and thermal therapy functions. There is no need to introduce additional contrast agents, and the embolism of the microspheres can be monitored in real time to correct ectopic embolism in a timely manner. The high crosslinking outer shell provides the microspheres with the required strength, while strengthening the encapsulation of the internal magnetic particles, improving the stability during storage and making it less likely to leak.
[0010] In addition, since embedding magnetic nanoparticles will increase the strength of the microspheres and reduce toughness, by embedding the magnetic nanoparticles in an inner core with a low degree of cross-linking and providing an outer shell with a high degree of cross-linking, the internal and external cross-linking degrees are regulated so that the microspheres have both good strength and toughness and will not agglomerate or clog the catheter during delivery, thereby making the catheter passability and the embolization effect in the blood vessel better.
[0011] In addition, the use of a specific cross-linking agent to introduce a phosphate drug-carrying group can quickly electrostatically adsorb with positively charged drug molecules to form a drug-carrying unit, completing the synergistic treatment of thermotherapy, chemotherapy, and embolization. The degradation rate of the core material of the core-shell structure is greater than the degradation rate of the shell material, so that the microspheres can have a good embolization effect during the period when the shell is completely degraded, and then the core is rapidly degraded to avoid ectopic diffusion of small-size spheres and foreign body inflammation. All components of the microspheres and their degradation products can be quickly absorbed or metabolized by the human body and have excellent biocompatibility. The entire preparation method is simple and environmentally friendly, can be mass-produced, and has significant functional effects.
[0012] In some embodiments of the present application, the magnetic nanoparticles account for 1% to 20% of the mass of the first starch.
[0013] In the above technical solution, the proportion of magnetic nanoparticles in the core will also affect the degree of crosslinking of the core. The smaller the proportion of magnetic nanoparticles, the greater the concentration of the first starch, the higher the degree of crosslinking, and the slower the degradation rate of the corresponding core.
[0014] In some embodiments of the present application, the magnetic nanoparticles are magnetic Fe 3 O4 Nanoparticles, magnetic Fe 3 O 4 The nanoparticles were prepared by solvothermal method.
[0015] In the above technical solution, the magnetic Fe 3 O 4 Nanoparticles have special magnetic properties such as superparamagnetism and high magnetic susceptibility, and have unique physical properties, biocompatibility, stability, etc., and can be effectively used in imaging and thermal therapy. 3 O 4 The nanoparticles have regular morphology, uniform size distribution and high saturation magnetization.
[0016] In some embodiments of the present application, the mass ratio of the first starch to the second starch is (1:1)-(1:3).
[0017] In the above technical solution, the dosage of the first starch and the second starch can correspond to the thickness of the inner core and the outer shell of the microsphere, and further correspond to the degradation time of the inner core and the outer shell. Therefore, the degradation time difference between the inner and outer layers of the microsphere can be controlled by the feed ratio of the first starch and the second starch.
[0018] In some embodiments of the present application, both the first starch and the second starch are amylopectin.
[0019] In the above technical solution, amylopectin has more cross-linking sites, and using amylopectin as both the first starch and the second starch is conducive to obtaining better-shaped microspheres.
[0020] In some embodiments of the present application, before the water phase is prepared, the method further includes: gelatinizing the first starch and the second starch respectively.
[0021] In the above technical solution, starch granules are broken down by gelatinization reaction to form single starch molecules, which are convenient for entanglement, coating and cross-linking to form a three-dimensional network structure.
[0022] In some embodiments of the present application, the reverse suspension polymerization process includes:
[0023] Under stirring conditions, slowly add the water phase to the oil phase, and react at 30-40° C. for 10-20 minutes; add the second cross-linking agent and the second starch, and react at 40-55° C. for 18-24 hours.
[0024] In the above technical solution, the reverse suspension polymerization process includes two stages. First, the first starch and the first crosslinking agent of the mixed magnetic nanoparticles are preliminarily polymerized to form an inner core that embeds the magnetic nanoparticles. Then, the second crosslinking agent and the second starch are added to react on the surface of the inner core to form an outer shell with a high degree of crosslinking.
[0025] In a second aspect, the present invention provides a magnetic degradable starch microsphere with a core-shell structure, which is prepared by the above preparation method. The degradation rate of the core material of the magnetic degradable starch microsphere is greater than the degradation rate of the shell material.
[0026] In some embodiments of the present application, the mass ratio of the core material to the shell material is (1:1)-(1:3).
[0027] In a second aspect, the embodiments of the present application also provide a use of magnetic degradable starch microspheres as embolic agents carrying chemotherapy drugs for TACE treatment.
[0028] The magnetic degradable starch microspheres have the functions of thermotherapy, chemotherapy and embolization. The magnetic nanoparticles embedded inside are not easy to leak and can be stored stably for a long time. They have good strength and toughness, are not easy to break or block the catheter during delivery, and have good catheter permeability. In addition, due to the large number of phosphate groups, chemotherapy drugs can be quickly loaded, so they can be effectively used in TACE treatment to carry embolic agents for chemotherapy drugs. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0030] Figure 1 This is a process flow chart of the method for preparing magnetic degradable starch microspheres with a core-shell structure provided in an embodiment of the present application.
[0031] Figure 2 This is a comparison chart of the iron content of the microspheres prepared in the examples of the present application and the comparative examples after accelerated aging for half a year.
[0032] Figure 3 This is a comparison chart of the iron content of the microspheres prepared in the examples of the present application and the comparative examples after accelerated aging for one year.
[0033] Figure 4 This is a test diagram of the drug loading performance of the magnetic degradable starch microspheres prepared in Example 1 of the present application.
[0034] Figure 5 This is an optical micrograph of the magnetic degradable starch microspheres prepared in Example 1 of the present application.
[0035] Figure 6 This is an optical micrograph of the magnetic degradable starch microspheres loaded with drugs prepared in Example 1 of the present application. DETAILED DESCRIPTION
[0036] Figure 1 This is a process flow chart of the preparation method of magnetic degradable starch microspheres with core-shell structure provided in the embodiment of the present application. Figure 1 The method for preparing magnetic degradable starch microspheres with a core-shell structure provided in the present application comprises the following steps:
[0037] S110, aqueous phase preparation: mixing the first starch, magnetic nanoparticles and the first cross-linking agent in a certain proportion to obtain an aqueous phase; wherein the mass ratio of sodium trimetaphosphate to sodium tripolyphosphate in the first cross-linking agent is (5-15):(85-95).
[0038] The first starch may be amylopectin. For example, the first starch may be corn amylopectin, potato amylopectin, sweet potato amylopectin, or the like.
[0039] Before the aqueous phase is prepared, the method further includes: gelatinizing the first starch and the second starch respectively. Specifically, the starch is heated and stirred in an alkaline aqueous solution until gelatinization and transparency are achieved. The alkaline aqueous solution may be a sodium hydroxide aqueous solution, the mass concentration may be 0.5wt%, the heating temperature may be 80°C, and the stirring time may be 1h.
[0040] The magnetic nanoparticles account for 1% to 20% of the mass of the first starch. The proportion of the core magnetic particles will also affect the cross-linking strength of the inner core. The thicker the starch, the stronger the cross-linking strength and the slower the degradation of the inner core.
[0041] The magnetic nanoparticles can be Fe 3 O 4 , Fe 2 O 3 , FeCo or CoFe 2 O 4 Preferably, the magnetic nanoparticles are Fe 3 O 4 , magnetic Fe 3 O 4 The nanoparticles can be prepared by a solvothermal method. Specifically, the method may include the following steps: using ferric chloride as an iron source, sodium acetate as a precipitant, sodium citrate as an electrostatic stabilizer, and ethylene glycol as a solvent and a reducing agent, reacting under high temperature and high pressure to prepare magnetic Fe 3 O 4 Nanoparticles. Magnetic Fe prepared by solvothermal method 3 O 4 The nanoparticles have regular morphology, uniform size distribution and high saturation magnetization.
[0042] The process of water phase configuration further includes: mixing the gelatinized starch and the magnetic nanoparticles by ultrasonic stirring, so that the magnetic nanoparticles are evenly dispersed in the gelatinized starch.
[0043] S120, oil phase preparation: mixing an oil-soluble solvent and an oil-soluble dispersant to obtain an oil phase.
[0044] The oil-soluble solvent may be n-decane, and the oil-soluble dispersant may be Span-60 and Tween-60. The mass ratio of Span-60 to Tween-60 is (1-3):(0.25-0.5).
[0045] S130, reverse suspension polymerization: adding the water phase to the oil phase, reacting for a period of time, adding the second cross-linking agent and the second starch, heating to a predetermined temperature, and obtaining magnetic degradable starch microspheres with a core-shell structure after the reaction is completed; wherein the mass ratio of sodium trimetaphosphate to sodium tripolyphosphate in the second cross-linking agent is (85-95):(5-15).
[0046] In the embodiment of the present application, a mixture of sodium trimetaphosphate and sodium tripolyphosphate is used as a cross-linking agent to emulsify cross-linked starch. Sodium trimetaphosphate and sodium tripolyphosphate have multiple phosphate groups. When cross-linked with starch, the phosphate groups react with the hydroxyl groups in the starch molecules to form phosphate bonds, thereby increasing the connection between starch molecules and forming a three-dimensional network structure. In addition, the sodium ions in sodium trimetaphosphate and sodium tripolyphosphate can ionically bond with the hydroxyl groups in the starch molecules, further enhancing the connection between starch molecules. In addition, the cross-linking reaction introduces a large number of negatively charged phosphate groups into the starch polymer chain segment, so that the prepared starch microspheres can quickly electrostatically adsorb with positively charged drug molecules to form drug-carrying units.
[0047] In the embodiment of the present application, the second starch and the first starch are both amylopectin. Preferably, the first starch and the second starch are both gelatinized starch, which is conducive to obtaining better-shaped microspheres.
[0048] In the above implementation process, different positions have different crosslinking degrees and components, which in turn produce different degradation rates, and the degradation rate of the material is usually negatively correlated with the degradation time. After testing, the crosslinking system of sodium trimetaphosphate and sodium tripolyphosphate has a better effect of co-mixing, among which sodium trimetaphosphate has a stronger crosslinking effect on starch than sodium tripolyphosphate. The higher the mass proportion of sodium trimetaphosphate, the higher the crosslinking degree and the longer the degradation time. Selecting the core material as starch doped with magnetic particles and the first crosslinking agent mediated mainly by sodium tripolyphosphate can make the core degrade quickly after the shell of the microsphere is completely degraded, which is beneficial to reduce the occurrence of inflammation during embolization therapy. Selecting the shell material as pure starch and sodium trimetaphosphate as the second crosslinking agent mediated mainly by sodium trimetaphosphate can help the microsphere maintain a good embolization effect and strengthen the encapsulation of the core physical embedding particles. Therefore, by controlling the mass ratio of sodium trimetaphosphate and sodium tripolyphosphate in the first crosslinking agent and the second crosslinking agent, the crosslinking degree of the core and shell of the microsphere can be controlled accordingly, and then the degradation rate of the inner and outer layers can be regulated. By adjusting the degradation rate difference between the shell and the core, the degradation time of the embolic microsphere can be controlled.
[0049] The conditions of reverse suspension polymerization include: slowly adding the water phase to the oil phase under stirring, reacting at 30-40° C. for 10-20 minutes; adding the second crosslinking agent and the second starch, reacting at 40-55° C. for 18-24 hours.
[0050] In the embodiment of the present application, the reverse suspension polymerization is divided into two stages: first, the first starch fully mixed with magnetic particles and the first cross-linking agent are quickly mixed, and then slowly poured into the oil phase stirred at high speed to initially form the magnetic core of the microsphere. Then, the second cross-linking agent is added to the reaction system, the rotation speed is reduced, and the second starch without magnetic particles is poured in. The second starch in the solution will preferentially react with the interface of the already formed microspheres to form a highly cross-linked shell on the outer layer.
[0051] It can be understood that after the reverse suspension polymerization reaction is completed, the process further includes: removing the microspheres without magnetic particle cores by magnetic separation.
[0052] Among them, the mass ratio of the first starch to the second starch is (1:1)-(1:3). By controlling the feed ratio of the first starch to the second starch, the mass ratio (thickness) of the core and the shell can be controlled accordingly. The shell thickness of the microsphere can be regulated according to actual needs (usually the more shell material is used, the thicker the shell). The mass proportion of the shell material is positively correlated with the degradation time of the entire microsphere, and the degradation time of the entire microsphere can also be controlled by regulating the mass ratio of the core material and the shell material.
[0053] This application uses starch and sodium trimetaphosphate (STP) and sodium tripolyphosphate (STP) to form core-shell components with different crosslinking degrees through chemical crosslinking based on the emulsification crosslinking method, and prepares embolic microspheres with uniform size and good biocompatibility, which have the following advantages: (1) The low-crosslinking core physically embeds magnetic nanoparticles, so that the microspheres have both magnetic imaging and thermal therapy functions, without the need to introduce additional contrast agents, and the embolism of the microspheres can be monitored in real time to correct ectopic embolism in a timely manner. (2) The shell with a high degree of crosslinking provides the microspheres with the required strength, while strengthening the encapsulation of the internal magnetic particles, improving the stability during storage, and making it less likely to leak. (3) The magnetic nanoparticles are embedded in the core with a low degree of crosslinking, while the shell has a high degree of crosslinking. The internal and external crosslinking degrees are regulated so that the microspheres have both good strength and toughness, and will not agglomerate or block the catheter during delivery, making its catheter passability and embolization effect in the blood vessel more excellent. (4) The phosphate drug-carrying group is introduced by a specific cross-linking agent, which can quickly electrostatically adsorb with positively charged drug molecules to form a drug-carrying unit, completing the synergistic treatment of thermotherapy, chemotherapy, and embolization. (5) The degradation rate of the shell material of the core-shell structure is greater than the degradation rate of the core material, so that the microspheres can have a good embolization effect during the period of complete degradation of the shell, and then the core is rapidly degraded to avoid ectopic diffusion of small-size spheres and foreign body inflammation. (6) All components of the microspheres and their degradation products can be quickly absorbed or metabolized by the human body and have excellent biocompatibility. (7) The preparation method is simple and environmentally friendly, can be mass-produced, and has significant functional effects.
[0054] In addition, the present application also provides a magnetic degradable starch microsphere with a core-shell structure prepared by the above preparation method, wherein the degradation rate of the core material is greater than the degradation rate of the shell material, wherein the mass ratio of the core material to the shell material is (1:1)-(1:3).
[0055] The magnetic degradable starch microspheres with a core-shell structure have both strength and toughness on the basis of multifunctionality and excellent biosafety. They can be used as embolic agents carrying chemotherapy drugs during transarterial catheter chemoembolization (TACE) treatment and have good application prospects.
[0056] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0057] In the following examples and comparative examples, the magnetic Fe 3 O 4The configuration methods of the nanoparticles, the first cross-linking agent, the second cross-linking agent and the gelatinized starch are respectively as follows:
[0058] (1) Preparation of magnetic Fe 3 O 4 Nanoparticles: 0.8 g ferric chloride, 0.25 g sodium citrate, and 1.5 g sodium acetate were dissolved in 30 mL ethylene glycol and stirred evenly by magnetic stirring. Then, the mixture was transferred to a 50 mL reactor and reacted at 200 °C for 10 h. After cooling to room temperature, the mixture was washed three times with deionized water and dried in a vacuum oven at 60 °C for 12 h to obtain magnetic Fe 3 O 4 Nanoparticles.
[0059] (2) Preparation of the first cross-linking agent: Weigh 20 g of sodium tripolyphosphate and 2 g of sodium trimetaphosphate, boil in 100 mL of distilled water, stir thoroughly to dissolve, let stand and cool to room temperature, filter, and seal for later use.
[0060] (3) Preparation of the second cross-linking agent: Weigh 20 g of sodium trimetaphosphate and 2 g of sodium tripolyphosphate, boil in 100 mL of distilled water, stir thoroughly to dissolve, let stand and cool to room temperature, filter, and seal for later use.
[0061] (4) Preparation of gelatinized starch: Weigh 30 g of corn amylopectin, add 300 mL of 0.5 wt% sodium hydroxide aqueous solution at room temperature, stir and mix thoroughly and continue stirring, slowly raise the temperature to 80°C and continue for 1 hour. The white opaque turbid liquid turns into a light yellow viscous liquid, and cools to room temperature for use. The first starch and the second starch in the examples and comparative examples are both gelatinized starch.
[0062] Example 1
[0063] This embodiment provides a magnetic degradable starch microsphere with a core-shell structure, and the preparation method thereof comprises the following steps:
[0064] Prepare the aqueous phase: 10g gelatinized starch and 0.6g magnetic Fe 3 O 4 The nanoparticles were mixed and ultrasonically stirred for 10 minutes to make the magnetic particles evenly dispersed in the gelatinized starch. Then 7 mL of the first cross-linking agent was added thereto and stirred at high speed for 1 minute.
[0065] Prepare the oil phase: weigh 1000g of n-decane, add 10g of Span-60 and 2.5g of Tween-60, heat to boil and stir thoroughly to mix evenly, seal and cool to room temperature for later use.
[0066] Reverse suspension polymerization: Take 240mL of oil phase in a flask, maintain 35°C, slowly pour the water phase into the oil phase under stirring at a speed of 300rpm, and react for 15min. Then, pour 10mL of the second cross-linking agent into the reaction system, and then slowly pour 40g of gelatinized starch into the reaction system, raise the reaction temperature to 55°C, react for 20h, add a certain amount of ethyl acetate, filter, and wash with ethyl acetate to remove oil-soluble impurities, and then use a magnet to separate the microspheres that are not wrapped in the magnetic core. Finally, rinse and sieve with purified water to obtain magnetic degradable starch microspheres with a core-shell structure.
[0067] The preparation methods of other embodiments and comparative examples are substantially the same as those of embodiment 1, except that some preparation conditions are different, as shown in Table 1:
[0068] Table 1 Partial preparation conditions of Examples and Comparative Examples
[0069]
[0070] Test Example 1
[0071] The surface properties of the microspheres prepared in the examples and comparative examples were tested. The particle size of the microspheres was 200-300 μm. The specific test results are as follows:
[0072] (1) Surface strength / compression resilience: The microspheres were spread on a slide to form a single layer, and their strength and elasticity were measured using a texture analyzer (TA-XTplusC). Strength was defined as the maximum force during compression of 30% and 50%, and elasticity was defined as whether the microspheres could recover their spherical shape after being compressed by a certain percentage.
[0073] (2) Suspension: Take 2 mL of microspheres, mix them evenly until they reach a stable state, and use a 20 mL syringe to perform vertical tube timing to observe the suspension state of the microspheres.
[0074] (3) Catheter permeability: Connect the syringe containing microspheres to a 1.8F microcatheter, place the tail end of the microcatheter into a centrifuge tube, and then perform a pulse injection at a rate of 1 mL / 1 min. During the injection, observe the state of the microspheres when they enter the microcatheter and the state of the microspheres when they exit the microcatheter and enter the centrifuge tube (dispersion, adhesion, clumping, wall adhesion, tube blockage), and then record them.
[0075] The above test results are shown in Table 2:
[0076] Table 2 Surface performance test results of the embodiments and comparative examples
[0077]
[0078] As can be seen from Table 1, the degree of crosslinking of the inner and outer shells of the microspheres and the embedding position of the magnetic nanoparticles will affect the surface properties of the microspheres. In Comparative Example 1, the degree of crosslinking of the core layer is greater than that of the outer shell layer, which will significantly reduce the surface strength and elasticity of the microspheres. In Comparative Example 2, the magnetic nanoparticles are embedded in the outer shell, which increases the strength of the outer shell but reduces the toughness, and there is a risk of fragmentation and clogging in the catheter. In Comparative Example 3, magnetic nanoparticles are embedded in both the inner core and the outer shell of the microspheres, which will lead to a decrease in its elasticity, reduced surface properties, and easy wall adhesion in the catheter. In Comparative Example 4, no magnetic nanoparticles are added, the surface properties are slightly reduced, and it does not have magnetic imaging and thermal therapy functions.
[0079] Test Example 2
[0080] The microspheres prepared in the examples and comparative examples were subjected to an aging stability test, and the test method included: a simplified aging formula established according to the Arrhenius reaction rate function:
[0081]
[0082] Among them, AAT: accelerated aging time; RT: real-time aging time; Q 10 : Aging coefficient when the temperature rises or falls by 10°C; T AA : Accelerated aging temperature; T RT : Preset actual storage temperature.
[0083] The microspheres were placed in a 55°C incubator for 23 days and 46 days to simulate the accelerated aging results of 0.5 years and 1 year at room temperature. The test results are shown in Table 3.
[0084] Due to Fe 2+ It can form a red complex with 1,10-phenanthroline, and its absorbance is measured at 510nm. 3+ Reduction to Fe 2+ The iron content test can then quantitatively characterize the leakage of magnetic particles in the microsphere preservation solution. Figure 2 and Figure 3 shown.
[0085] Table 3 Aging stability test results of the embodiments and comparative examples
[0086]
[0087] From Table 3, Figure 2 and Figure 3It can be seen that in Comparative Example 2, magnetic nanoparticles were embedded in the shell, and magnetic particle leakage occurred after accelerated aging for half a year, and magnetic particle leakage and microsphere agglomeration occurred in Comparative Examples 1-2 after accelerated aging for one year, indicating that when the physically encapsulated magnetic particles are on the surface of the microspheres, as the storage time increases, some magnetic particles will diffuse into the storage liquid medium. At the same time, after the starch surface is doped with magnetic particles, it may also affect its surface interaction force, reduce surface performance, and easily agglomerate during storage. In the embodiment of the present application, the magnetic nanoparticles are embedded in the core with a low cross-linking degree through the core-shell cross-linking degree design, which can effectively prevent leakage.
[0088] Test Example 3
[0089] The microspheres prepared in Example 1 and Comparative Examples 1-4 were subjected to a degradation test. The specific test process was as follows: 1 mL of 200-300 μm microspheres were added to 9 mL of artificial plasma and incubated on a shaker at 37° C. After different time intervals T, 0.5 mL was taken and mixed and diluted to 1 mL. The Z average particle size was analyzed by dynamic light scattering (DLS). T :D 0 The ratio of is taken as the degradation standard, where D 0 is the diameter of the undegraded microspheres, D T is the diameter of the microsphere after degradation T time. The above test results are shown in Table 4.
[0090] Table 4 Degradability test results of the embodiments and comparative examples
[0091] Group 24h 48h 60h 72h 80h 88h 96h 104h Example 1 91.64% 94.82% 87.63% 61.73% 38.57% 13.62% 2.63% 0 Comparative Example 1 82.76% 60.63% 45.64% 37.65% 31.85% 9.53% 0.64% 0 Comparative Example 2 88.76% 81.83% 75.29% 50.82% 31.63% 15.94% 6.65% 0 Comparative Example 3 91.83% 85.98% 81.83% 58.84% 37.45% 16.83% 5.72% 0 Comparative Example 4 91.01% 98.47% 88.75% 67.73% 46.76% 20.53% 9.12% 2.93%
[0092] As can be seen from Table 4, the microspheres prepared in the examples of the present application have a slow degradation rate in the first 72 hours due to the high cross-linking degree of the shell, while the core is doped with magnetic nanoparticles and has a low cross-linking degree, so the degradation rate is fast. Therefore, the microspheres prepared in the examples of the present application can play the trinity of thermotherapy, chemotherapy, and embolization in the process of slow degradation of the shell layer, and after the shell layer is completely degraded, the core can be quickly degraded, which can avoid ectopic diffusion of small-size balls and foreign body inflammation.
[0093] Test Example 4
[0094] As a vascular implant material, the biocompatibility of microspheres is an important indicator for application evaluation. The microspheres were mixed with a physiological saline solution containing 4% red blood cells, and the absorbance value of the supernatant at 545nm was tested by spectrophotometry, and the hemolysis rate was calculated to test its hemolysis performance. A hemolysis rate below 5% indicates that the biocompatibility of the implant material meets the standard. The test results are shown in Table 5:
[0095] Table 5 Hemolysis rate test results of the embodiments and comparative examples
[0096] Group Example 1 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Hemolysis rate 2.16% 2.07% 4.03% 2.98% 1.39%
[0097] Since the microsphere material is composed only of starch, sodium tripolyphosphate, sodium trimetaphosphate, and magnetic nanoparticles, the components have been proven to be safe and non-toxic. As shown in Table 5, the hemolysis rates of the microspheres in the embodiments and comparative examples are all lower than 5%, indicating that the degradable magnetic drug-loaded microsphere system with a core-shell structure designed by us has excellent biosafety.
[0098] Test Example 5
[0099] Drug loading performance test, loading doxorubicin, the specific test method includes: taking 2g of the microspheres of Example 1, loading doxorubicin (40mg / mL, 5mL), taking samples at regular intervals, testing the drug residue in the solution by high performance liquid chromatography, and calculating the drug loading rate and encapsulation rate.
[0100] Depend on Figure 4 It can be seen that the magnetic degradable starch microspheres prepared in Example 1 of the present application can quickly load drugs, with high encapsulation efficiency and drug loading. The drug loading of doxorubicin can reach 125 mg / g in 30 minutes. Figure 5 and Figure 6 It can be seen that the drug is uniformly loaded in the microspheres.
[0101] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application.
Claims
1. A method for preparing magnetic degradable starch microspheres with a core-shell structure, characterized in that: The following steps are involved: Aqueous phase configuration: mixing the first starch, magnetic nanoparticles and the first cross-linking agent in a certain proportion to obtain an aqueous phase; Oil phase preparation: mixing an oil-soluble solvent and an oil-soluble dispersant to obtain an oil phase; Reverse suspension polymerization: adding the water phase to the oil phase, reacting for a period of time, adding a second cross-linking agent and a second starch, heating to a predetermined temperature, and obtaining magnetic degradable starch microspheres with a core-shell structure after the reaction is completed; Among them, the mass ratio of sodium trimetaphosphate to sodium tripolyphosphate in the first cross-linking agent is (5-15):(85-95), and the mass ratio of sodium trimetaphosphate to sodium tripolyphosphate in the second cross-linking agent is (85-95):(5-15).
2. The preparation method according to claim 1, characterized in that: The magnetic nanoparticles account for 1% to 20% of the mass of the first starch.
3. The preparation method according to any one of claims 1 to 2, characterized in that: The magnetic nanoparticles are magnetic Fe3O4 nanoparticles, and the magnetic Fe3O4 nanoparticles are prepared by a solvent thermal method.
4. The preparation method according to claim 1, characterized in that: The mass ratio of the first starch to the second starch is (1:1)-(1:3).
5. The preparation method according to claim 1 or 4, characterized in that: The first starch and the second starch are both amylopectin.
6. The preparation method according to claim 1, characterized in that: Before the water phase is prepared, the method further includes: gelatinizing the first starch and the second starch respectively.
7. The preparation method according to claim 1, characterized in that: The reverse suspension polymerization process comprises: Under stirring conditions, slowly add the water phase to the oil phase, and react at 30-40° C. for 10-20 minutes; add the second cross-linking agent and the second starch, and react at 40-55° C. for 18-24 hours.
8. A magnetic degradable starch microsphere prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The degradation rate of the core material of the magnetic degradable starch microsphere is greater than the degradation rate of the shell material.
9. The magnetic degradable starch microspheres according to claim 8, characterized in that: The mass ratio of the core material to the shell material is (1:1)-(1:3).
10. Use of the magnetic degradable starch microspheres as claimed in claim 9 as embolic agents carrying chemotherapy drugs for TACE treatment.
